Factors that influence truancy among secondary school students in Melaka Tengah / Mohamad Shafie Suleiman and Mohamad Shahril Fiqry Roslan - Suleiman, Mohamad Shafie; Roslan, Mohamad Shahril Fiqry (Faculty of Administrative Science and Policy Studies, 2013)
This study examines the factor that influences truancy among secondary students in Melaka Tengah. Reviews of the literature show that there are few factors that influenced the truancy among secondary students itself. Studies done by other researchers were used as guidelines to determine what factors that can be tested in this study, and the factors are family matters, school management, and also peer pressure. A questionnaire survey was distributed to 338 respondent among young people aged from 13years old to 16 years old. A total of 338 valid responses were obtained. Data analysis shows that significant relationship exists between three factors toward truancy among secondary students in Melaka Tengah. School management emerged as the most influential factor that influences truancy among secondary students in Melaka Tengah.